1996
DOI: 10.1177/08959374960100022701
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells: A Novel Cellular Component of the Rat Incisor Enamel Organ Appearing in the Late Stages of Enamel Maturation

Abstract: Immunocompetent cells in the enamel organ of rat incisors were examined immunohistochemically using OX6, ED1, and ED2 monoclonal antibodies known to recognize the Class II MHC molecules, a monocyte-macrophage lineage, and residential macrophages, respectively. The OX6 immunopositive cells (MHC cells) were located exclusively in the enamel maturation zone. MHC cells increased in number in the incisal direction and occasionally extended cytoplasmic processes deep into the ameloblast layer. Migration of MHC cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
2
15
0
1
Order By: Relevance
“…During enamel maturation, a considerable number of ameloblasts are lost, as well as the transition stage [10,18,20]. In the transition stage, about 25% of ameloblasts show degeneration and necrosis and are phagocytosed by intermediate layer cells or macrophages [9,10,18].…”
Section: Discussionmentioning
confidence: 99%
“…During enamel maturation, a considerable number of ameloblasts are lost, as well as the transition stage [10,18,20]. In the transition stage, about 25% of ameloblasts show degeneration and necrosis and are phagocytosed by intermediate layer cells or macrophages [9,10,18].…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cells in the enamel organ of the maturation zone of rat incisors are scarce in juvenile animals, whereas numerous dendritic cells are present in the adult animals (Takano et al 1996). This study showed the presence of round cystatin C-positive cells in the incisor apical bud of the newborn rat.…”
Section: Discussionmentioning
confidence: 64%
“…Because of its bulbous morphology, the proliferation zone has been proposed as the apical bud (Ohshima et al 2003), and this latter terminology is used in this report. In more advanced zones of the enamel organ of rat incisor, that is the transition and maturation zones, many dendritic cells invade the epithelial layer (Nishikawa and Sasaki 1996;Takano et al 1996). In particular, in the late maturation zone, numerous dendritic cells are localized in the epithelial papillary layer (Takano et al 1996).…”
mentioning
confidence: 99%
See 2 more Smart Citations